Credit Limit of Unsecured Consumer Lending: Evidence from Micro Data - Suwinto Johan; Calista Endrina Dewi (Economics and Finance in Indonesia, 2021)
As credit card debts have increased in Indonesia over the past ten years, concerns over the impulsive buying behavior of Indonesian credit card holders have emerged. Therefore, more attention must be paid to credit risk management of banks as it plays an important role in analyzing the possibility of losses due to the inability of prospective borrowers to repay debts. This study provides empirical evidence about the prudence of commercial banks in Greater Jakarta in offering credit card limits. Using primary micro-data collected from credit card applications submitted to the largest foreign private bank providing retail credit in the Greater Jakarta area in 2019, this study employed multiple regression model to analyze the determinants of credit card limits in the Greater Jakarta. Our empirical findings suggest that age, home location, income, type of industry, and office location of prospective borrowers significantly influence credit card limits. Commercial banks in the Greater Jakarta, thus, have been prudent in offering credit card limits.